2020
DOI: 10.47176/mjiri.34.41
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of allopurinol versus febuxostat in the treatment of gout patients: A systematic review

Abstract: Allopurinol and febuxostat are urate-lowering drugs used for the long-term treatment of gout through reducing the uric acid levels. More studies have indicated cost-effectiveness of febuxostat in reducing serum urate concentration and showed that it alleviates gout flares better than allopurinol. However, related studies have reported conflicting results about the cost-effectiveness of these drugs. →What this article adds:Febuxostat is more cost-effective than allopurinol in all treatment sequences in studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…With rapid economic development and urbanization, the burden of gout has increased in many parts of the world, and the burden on the health system has also gradually increased, 6 becoming an increasingly serious public health problem. The overall planning of the health system requires careful assessment of the epidemiology of gout.…”
Section: Introductionmentioning
confidence: 99%
“…With rapid economic development and urbanization, the burden of gout has increased in many parts of the world, and the burden on the health system has also gradually increased, 6 becoming an increasingly serious public health problem. The overall planning of the health system requires careful assessment of the epidemiology of gout.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Moreover, high SUA levels can cause significant economic losses to patients, including direct (eg medical consultation fees) and indirect (eg loss of productivity) costs. [7][8][9] However, there are relatively few published studies on the association between SUA levels in gout patients and examination fees and complications. Therefore, this study aimed to analyze the relationship between different SUA levels of patients with gout and their examination fees and complications using a cross-sectional study to provide a relevant basis for the optimal diagnosis, treatment, and management of patients with gout at different SUA levels and to maximize clinical and economic benefits for patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that gout and hyperuricemia are related to various complications, such as hypertension, coronary heart disease, myocardial infarction, kidney diseases, and liver diseases 4–6 . Moreover, high SUA levels can cause significant economic losses to patients, including direct (eg medical consultation fees) and indirect (eg loss of productivity) costs 7–9 . However, there are relatively few published studies on the association between SUA levels in gout patients and examination fees and complications.…”
Section: Introductionmentioning
confidence: 99%